A monetary policy strategy in good and bad times: lessons from the recent past. Issue 74 (12th April 2013) - Fahr, Stephan; Motto, Roberto; Rostagno, Massimo; Smets, Frank; Tristani, Oreste
Summary We evaluate the ECB's monetary policy strategy against some of the underlying economic features of the eurozone, in normal times and during the financial crisis. We show that in the years preceding the crisis the ECB's emphasis on monetary indicators and deliberate avoidance of excessive activism were justified by the underlying macroeconomic conditions that the ECB faced in the eurozone and contributed to avoid more volatile patterns of inflation and economic activity. After the collapse of financial intermediation in late 2008, the strategy of the ECB was to adopt several non‐standard policy measures. According to our quantitative evaluation of the impact of the main non‐standard policies decided in October 2008 and in May 2009, which notably did not include entering commitments regarding the future path of the policy rate, such measures have significantly contributed to preserving price stability and forestalling a more disruptive collapse of the macroeconomy. — Stephan Fahr, Roberto Motto, Massimo Rostagno, Frank Smets and Oreste Tristani